Work-From-Anywhere: The Productivity Effects of Geographic Flexibility - Choudhury, Prithwiraj; Foroughi, Cirrus; Larson, Barbara (2020)
ABSTRACT An emerging form of remote work allows employees to work-from-anywhere, so that the worker can choose to live in a preferred geographic location. While traditional work-from-home (WFH) programs offer the worker temporal flexibility, work-from-anywhere (WFA) programs offer both temporal and geographic flexibility. WFA should be viewed as a nonpecuniary benefit likely to be preferred by workers who would derive greater utility by moving from their current geographic location to their preferred location. We study the effects of WFA on productivity at the United States Patent and Trademark Office (USPTO) and exploit a natural experiment in which the implementation of WFA was driven by negotiations between managers and the patent examiners’ union, leading to exogeneity in the timing of individual examiners’ transition from a work-from-home to a work-from-anywhere program. This transition resulted in a 4.4 percent increase in output without affecting the incidence of rework. We also report results related to a plausible mechanism: an increase in observable effort as the worker transitions from a WFH to a WFA program. We employ illustrative field interviews, micro- data on locations, and machine learning analysis to shed further light on geographic flexibility, and summarize worker, firm, and economy-wide implications of provisioning WFA. Keywords geographic flexibility, work-from-anywhere, remote work, telecommuting, worker mobility ABOUT THE AUTHOR/S Prithwiraj Choudhury Harvard Business School pchoudhury@hbs.edu Prithwiraj (Raj) Choudhury is the Lumry Family Associate Professor at the Harvard Business School. He was an Assistant Professor at Wharton prior to joining Harvard. His research is focused on studying the Future of Work, especially the changing Geography of Work. In particular, he studies the productivity effects of geographic mobility of workers, causes of geographic immobility and productivity effects of remote work practices such as ‘Work from anywhere’ and ‘All-remote’. Cirrus Foroughi Harvard Business School cforoughi@hbs.edu Barbara Larson Northeastern University b.larson@northeastern.edu New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s)